Peran Mahasiswa Komunikasi dalam Mengelola Event Festival Komunikasi sebagai Praktik Public Relations - Aulia Nazila; Rissa Sabrina Putri; Miftahul Janna; Abdur Razzaq; M. Yudistira (Journal of Innovative and Creativity, 2025)
This research aims to analyze the role of Communication Science students at UIN Raden Fatah Palembang in organizing the 2025 Communication Festival as a practical application of Public Relations (PR). The students of class PR 2271 A, sixth semester, served as the core organizing committee, managing the event from planning to evaluation. They applied essential PR functions such as media relations, event management, digital publication,and crisis communication.This research employs a descriptive qualitative approach using a case study method.Data were collected through participatory observation, semi-structured interviews, and documentation, and analyzed using Miles and Huberman's interactive model.The findings reveal that the Communication Festival served as a real platform for students to implement PR theories and develop practical, hands-on experience aligned with Kolb's experiential learning model. Students demonstrated not only the ability to perform strategic communication tasks but also adaptability in facing communication challenges during the event. These findings highlight the importance of integrating theory and practice in communication education and the need to encourage experiential-based activities within the academic curriculum. The Communication Festival not only strengthened students'competencies but also contributed positively to the institutional image.